Embedded SoPC design with NIOS II processor and Verilog examples - Chu, Pong P., 1959- (Wiley, 2012)
"This book explores the unique hardware programmability of FPGA (field-programmable gate array)-based embedded systems, using a learning-by-doing approach to introduce the concepts and techniques for embedded SoPC (system on a programmable chip) systems with Verilog. The book contains a large number of practical examples to illustrate and reinforce the hardware and software design concepts and techniques, as well as a complete code listing and experiment problems. The book is designed for upper-level undergraduate and entry-level graduate students in computer engineering, as well as practicing engineers"--